The right of hot pursuit and maritime enforcement in malaysia: constraints and restraints - Hamid, Abdul Ghafur@Khin Maung Sein (s.n, 2012)
Although the right of hot pursuit is firmly established in international law, there exists much uncertainty over the precise boundaries of this rule. These uncertainties are particularly troublesome because they demand a delicate balancing of three imperatives of international law - state sovereignty, freedom of the seas, and enforcement of law and order. The present paper is an attempt to seek answers to these uncertainties on the basis of State practice and scholarly writings. After ascertaining the law governing the right of hot pursuit, the paper proceeds to examine the position of maritime enforcement in Malaysia and the constraints and restraints of the Malaysian Maritime Enforcement Agency (MMEA). The paper concludes that there is an urgent need to reform the MMEA statute in order to effectively maintain law and order in the Malaysian maritime zones. The paper comes out with suggested amendments to the appropriate provisions of the MMEA Act, including a new chapter on the right of hot pursuit, together with the justifications for these amendments.